High-grade squamous intraepithelial lesions in pregnant and non-pregnant women - Xavier-Junior, Jose Candido C. [UNESP]; Dufloth, Rozany Mucha [UNESP]; Vale, Diama B. do; Tavares, Thalita A. [UNESP]; Zeferino, Luiz C. (Elsevier B.V., 2014)
Objectives: To evaluate if the prevalence of cervical smear results varies between pregnant and nonpregnant women stratified by age group.Study design: Observational analytical study with a total sample of 1,336,180 pregnant and nonpregnant women, aged between 20 and 34 years, who underwent cervical cancer screening in the Primary Health Care of the national health system in the area of Campinas in Brazil during the period of 2005-2009. The source is the information system for cervical cancer screening. Data collected on abnormal cervical smears were analyzed using the Chi-square test and Fisher's exact test and the magnitude of the association between pregnancy and high-grade squamous epithelial lesions was analyzed by odds ratio (OR) and estimated values with confidence intervals (CI) of 95%.Results: 15,190 pregnant women and 395,961 non-pregnant women were analyzed and fulfilled the inclusion criteria. Regardless of age, no statistical differences were observed for high-grade squamous intraepithelial lesion prevalence (OR 0.90; CI 0.66-1.23). Taking into account the five-year age groups, however, low-grade squamous intraepithelial lesion was less prevalent in pregnant women aged 20-24 (OR 0.71; 0.54-0.95) and 25-29 years (OR 0.56; 0.35-0.89); also, atypical squamous cells of undetermined significance was more prevalent in non-pregnant women aged 25-29 years (OR 0.72; 0.54-0.97).Conclusion: The study showed that the cytological prevalence of high-grade squamous intraepithelial lesion was similar in pregnant and non-pregnant women, regardless of age. The results indicate that there are no reasons for specific approaches to cervical cancer screening for pregnant women. The examination should be carried out only on pregnant women who have not been tested according to current recommendations. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Papanicolaou smear; Pregnancy; Cervical cancer screening; Cervical intraepithelial neoplasia; Age